DETERMINANTS OF LECTURER PERFORMANCE: THE ROLE OF TRANSFORMATIONAL LEADERSHIP, COMPETENCE, AND JOB SATISFACTION AT MUHAMMADIYAH UNIVERSITIES IN JAKARTA - Sunarti Sunarti; Iswan Iswan; Nazifah Husainah; Saiful Bahri; Herwina Bahar; Loretna Haryatno (Taksasila Edukasi Insani, 2025)
This study investigates the influence of transformational leadership and competence on lecturer performance, using job satisfaction as a mediating variable at Muhammadiyah universities in Jakarta. Prompted by the need to improve institutional rankings, this research employed a quantitative path analysis design with PLS-SEM on a sample of 250 permanent lecturers. The findings reveal that while competence directly and significantly enhances both job satisfaction and performance, transformational leadership's impact on performance is entirely indirect. Leadership significantly boosts job satisfaction, which in turn is a strong predictor of lecturer performance, acting as a full mediator. This study concludes that enhancing lecturer performance requires a dual strategy: directly developing lecturer competence while leveraging transformational leadership to cultivate a satisfying work environment, which is the essential pathway for leadership to translate into tangible performance outcomes.Keywords: Competence, Job Satisfaction, Leadership